(untitled) (Docentes 2.0 Journal, 2016)
The SWOT Analysis, also known as SWOT Analysis, is a methodology for studying the situation of a company or a project, analyzing its internal characteristics (Weaknesses and Strengths) and its external situation (Threats and Opportunities) in a square matrix. It is a tool to know the real situation in which an organization, company or project is, and plan a future strategy.